Improving i‐P3HB Processing Window: Solution‐Casting Blends With a‐P3HB and P34HB - Almustafa, Wael; Grishchuk, Sergiy; Sebastian, Jörg; Schubert, Dirk W.; Grun, Gregor (Journal of Applied Polymer Science, 2025)
Poly(3-hydroxybutyrate) (P3HB) is a biobased and biodegradable polymer that is primarily produced through biotechnological fermentation processes. Its high crystallinity of around 70% and low thermal stability hinder its processing and application in different sectors. In this work, blends of isotactic poly(3-hydroxybutyrate) (i-P3HB) with the chemically synthesized atactic poly(3-hydroxybutyrate) (a-P3HB) and poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P34HB) were prepared via solution casting. The thermal, mechanical, and morphological properties of the blends were analyzed to evaluate the influence of a-P3HB and P34HB on the processing window of i-P3HB. The obtained blends exhibited reduced glass transition temperatures, from 5.5°C for neat i-P3HB to around −53°C with 50 wt.% of a-P3HB, as well as reduced melting temperatures, reaching 155°C with 50 wt.% of a-P3HB. Furthermore, blends containing all three polymers exhibited also a significant decrease in the degree of crystallinity reaching 19% and an improved elongation at break of up to 70%. The reduced melting temperature facilitates processing at temperatures below the melting temperature of neat i-P3HB (175.5°C), avoiding its thermal degradation. Consequently, these blends broaden the processing window and enhanced the flexibility of i-P3HB, facilitating its application across various sectors, including packaging and textile